Civil Servant Disobedience: An Alternative Legal Strategy to Prevent Bureaucratic Pathology - Wibowo, Richo Andi (UI Scholars Hub, 2025)
This paper seeks to provide conceptual and empirical justifications for civil servants to engage in disobedience to curb bureaucratic pathology. Various civil servants have long complained that they face illegal instructions from their superiors. The cases discussed here are from public procurement, which has a dimension of political corruption, a recurring problem in many places in Indonesia. Thus, the problem shall be seen as a bureaucratic pathology rather than as maladministration. As the reporting of superiors to legal enforcers may be too risky, the disobedience can be accomplished by refusing to cooperate with superiors who give illegal instructions. The term 'superiors' here focuses on positions in government held by politicians, temporary positions obtained through elections, such as president, governor, mayor or regent, and temporary political positions given by appointment to a particular person, such as that of minister. There are four arguments in favour of civil servant disobedience. First, civil servant disobedience is rooted in the concept of civil disobedience, which has certain virtues and has been globally accepted. Second, legal justification dictates that civil servants' loyalty is not to their superiors but primarily to society and the law. Third, a cost–benefit analysis based on several court decisions, interviews and risk factor mapping reveals that the benefits to bureaucrats of following illegal instructions from politicians are less than the risks and sanctions. Fourth, from a religious sociological perspective, religion requires obedience only to God, not servitude to man or worldly interests. The justifications offered here for civil servant disobedience may be applicable to the Indonesian context and serve as food for thought for any country facing similar situations.